2022
DOI: 10.14569/ijacsa.2022.0130729
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Detection and Classification using Deep Learning Xception Algorithm

Abstract: Breast Cancer (BC) is one of the leading cause of deaths worldwide. Approximately 10 million people pass away internationally from breast cancer in the year 2020. Breast Cancer is a fatal disease and very popular among women globally. It is ranked fourth among the fatal diseases of different cancers, for example colorectal cancer, cervical cancer, and brain tumors. Furthermore, the number of new cases of breast cancer is anticipated to upsurge by 70% in the next twenty years. Consequently, early detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…For future work, they seek to improve the accuracy of the models with new tuning parameters and optimizers. In [27] they presented a model based on Xception for the detection of breast cancer in real-time. The InceptionV3 model, which is the best performing model in this work, can be extended to classify other diseases as [27] has done with good results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For future work, they seek to improve the accuracy of the models with new tuning parameters and optimizers. In [27] they presented a model based on Xception for the detection of breast cancer in real-time. The InceptionV3 model, which is the best performing model in this work, can be extended to classify other diseases as [27] has done with good results.…”
Section: Discussionmentioning
confidence: 99%
“…In [27] they presented a model based on Xception for the detection of breast cancer in real-time. The InceptionV3 model, which is the best performing model in this work, can be extended to classify other diseases as [27] has done with good results. The performance of the models can be improved with a larger amount of data.…”
Section: Discussionmentioning
confidence: 99%
“…Sivapriya, Kumar, et al, 2019 [24], compared SVM, logistic regression, naive Bayes, and random forest to determine their parallels and distinctions. Wisconsin's breast cancer dataset is used for comparative purposes (Abunasser, AL-Hiealy et al, 2022) [25]. The results of the evaluations showed that the random forest algorithm achieved the highest level of accuracy (99.76%) with the least amount of error.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [ 42 ] conducted another study on BC using the Xception method, a form of the DL model. The study found that the Xception algorithm accurately classified breast cancer histopathology images.…”
Section: Related Workmentioning
confidence: 99%